Crosstalk between Photoreceptor and Sugar Signaling Modulates Floral Signal Transduction - Matsoukas, Ianis G. (Frontiers in Physiology, 2017)
Over the past decade, integrated genetic, cellular, proteomic and genomic approaches have begun to unravel the surprisingly crosstalk between photoreceptors and sugar signaling in regulation of floral signal transduction. Although a number of physiological factors in the pathway have been identified, the molecular genetic interactions of some components are less well understood. The further elucidation of the crosstalk mechanisms between photoreceptors and sugar signaling will certainly contribute to our better understanding of the developmental circuitry that controls floral signal transduction. This article summarizes our current knowledge of this crosstalk, which has not received much attention, and suggests possible directions for future research.